Charitable giving as a gift exchange : evidence from a field experiment - Armin Falk (Center for Economic Studies and ifo Institute (CESifo), 2004)
This study reports data from a field experiment that was conducted to investigate the relevance of gift-exchange for charitable giving. Roughly 10,000 solicitation letters were sent to potential donors in the experiment. One third of the letters contained no gift, one third contained a small gift and one third contained a large gift. Whether a potential donor received a letter with or without a gift was randomly determined. We observe strong and systematic effects from including gifts. Compared to the no gift condition, the relative frequency of donations increased by 17 percent if a small gift was included and by 75 percent for a large gift. Consequently, including gifts was highly profitable for the charitable organization. The contribution of this paper is twofold: first, it shows that gift-exchange is important for charitable giving, in addition to the warm-glow motive. Second, the paper confirms the economic relevance of reciprocity by using field data. This extends the current body of research on reciprocity, which is almost exclusively confined to laboratory studies.
Keywords: C93; H41; D63; 330; charitable giving; field experiments; reciprocity; Spende; Motivation; Konsumentenverhalten